Time and cost constrained design of a simple step-stress accelerated life test under progressive Type-I censoring. Issue Volume 33:Issues 1(2021) (22nd August 2020) - Han, David
Abstract: With the engineering technology and manufacturing processes continuously improving, modern products and devices are becoming more sophisticated and reliable. On the other hand, conducting traditional life tests for these products at normal operating conditions has become almost impossible because of their extremely long lifespans. In this competing market, this is largely problematic as it could substantially delay introducing the newly developed products to the market, resulting in missed business opportunities and eventually loss of the market share. This problem is solved by accelerated life tests by subjecting the test units at higher stress levels than normal so that information on the desired lifetime parameters can be obtained more rapidly. The lifetime at the design condition is then estimated through extrapolation using an appropriate regression model. In this work, the design optimization of a simple step-stress accelerated life test under progressive Type-I censoring is investigated for assessing the reliability characteristics of a solar lighting device. Under the practical constraints that the test duration is pre-fixed for a scheduling purpose and the total experimental cost does not exceed a pre-specified budget, the design is formulated explicitly with non-uniform step durations. With the intermediate censoring taking place at the stress change time point, the existence of the optimal design is demonstrated for exponential lifetimes with a single stress variable under several design criteria including D -optimality, C -optimality, A -optimality, M -optimality, and E -optimality.